الإنسان والمسكن بين القيمة والحاجة - محمود سلمان; صيداوي وليد; بدر رنا (Latakia University Journal -Engineering Sciences Series, 2019)
تعددت مشاكل الإنسان من جراء التحضر العمراني وأهمها فقدان هذا الإنسان في الفراغ الحضري لقدرته على تلبية احتياجاته من خلال فراغ ومكونات وحجم مسكنه ،بل وعدم قدرته على المشاركة في بناء هذا المسكن.وأصبح المسكن عبارة عن " سلعة جاهزة " تُباع وتشترى دون أن يُتاح للفرد الفرصة للبحث عن ما يناسبه طبقاً لإمكانياته واحتياجاته مما أنتج تبايناً شديداً بين المتاح والمرغوب لتلبية ما يحتاجه الساكن. وعليه هدف الباحث إلى : 1ـ تجسيد مشاركة الإنسان في بناء مسكنه من خلال إيضاح أهمية مشاركته في تقدير احتياجاته والأساليب الممكنة لتحقيقها. 2ـ توضيح ضرورة إيجاد علاقة توازنية بين الفرد وأصحاب الاختصاصات المسؤولين عن تقدير الاحتياجات. يقوم البحث على ثلاثة أجزاء هي : 1ـ الجزء النظري: ويبحث في واقع العلاقة بين الساكن والمسكن في إطار القيمة والحاجة وبيان أهمية تقدير احتياجات الساكن من خلال تصرفه في تأمين احتياجاته الايوائية سواء في المناطق العشوائية أو في مناطق التوسّع في مدينة اللاذقية (مناطق ذوي الدخل المحدود والمتوسط).وتخلص الدراسة النظرية إلى تحديد العوامل التقييمية وفقا لتيرنر. والتي بتحليلها توضح مدى ملائمة المسكن لساكنه. 2ـ الجزء التحليلي: ويعتمد على تحليل واقع معاش عبر رصد العلاقة بين العوامل التقييمية وحالة الإسكان المختارة باستخدام طريقة تيرنر لاستنتاج ما يلي : ـ تحليل باعتماد العوامل التقييمية التي اقترحها( تيرنر) لمنطقة الإسكان العشوائي. ـ تحليل باعتماد العوامل التقييمية التي اقترحها( تيرنر) لمنطقة التوسع(مناطق ذوي الدخل المحدود والمتوسط). ـ بيان إمكانية الاستفادة من التحاليل السابقة في جدوى تواجد الفرد في تحديد احتياجاته في إطار إمكانياته، وكذلك في مجال مشاركته في عملية البناء. 3ـ الاستنتاجات: الخروج بمتجهات تدعو إلى ضرورة إعادة الفرد إلى معادلة البناء سواء في تقدير الاحتياجات أو توفير المطلوب لتحقيق علاقة أفضل بين الإنسان والمسكن في مناطق التحضّر وضمن إطار الموازنة بين القيمة والحاجة. Man’s problems have increased as a result of residential constructional development. The most important of these problems is Man’s loss of achieving his needs in terms of size, space and constituents of his residence, as well as his inability to take part in the construction of his residence. Man’s residence has become a ready-made commodity to be bought and sold without giving the chance to the individual to choose what suits him depending on his need and financial capability. This fact created a gap between offer and need. This search aims at: 1- Indicating the importance of Man’s share in the construction of his residence; through explaining the importance of this participation in figuring out his need and the possibility of achievement. 2- Explaining the need of striking a balance between the individual and those who are responsible for estimating Man’s requirements. The search consist of: 1- Theoretical Part: Discusses the relationship between Man and his residence within the framework of need and value. This part shows the importance of estimating the resident’s requirements through his behaviour in securing his residence within the legal or illegal residence areas of Lattakia (areas of those people of limited income). This part gives at the end the evaluating factors, as set by Turner, which shows, through analysis, the suitability of residence to the individual. 2- Analytical Part: Depends on Turner’s method of analyzing an existing relationship by noticing the evaluating factors of a chosen residence area so as to do the following: - Analyzing illegal residential areas. - Analyzing legal expansion residential areas (of those of limited income). - Showing the positive side of having the individual share in expressing his need and the construction process. 3- -Conclusions: Giving recommendations regarding the importance of including Man into the process of residential construction, so as to create a better relationship between Man and his residence within the framework of need and value.